Mineral waste recycling, sustainable chemical engineering, and circular economy - Haoxuan Yu; Izni Zahidi; Chow Ming Fai; Dongfang Liang; Dag Øivind Madsen (Results in Engineering, 2024)
The mineral processing industry is pivotal in natural resource extraction and historically contributes to environmental damages like land degradation and groundwater contamination. In the face of resource scarcity and environmental pollution, sustainable solutions are increasingly vital. The circular economy focuses on reusing, recycling, and reducing waste, which turns unwanted by-products into valuable assets. Sustainable chemical processes offer innovative solutions in waste material reclamation and integration into the production chain. These practices not only mitigate waste but also enable resource recovery, turning waste management costs into profits. Repurposing mineral waste reduces mining's environmental impact, lessens new mining needs, and yields economic advantages.